LIVRE INICIATIVA: fundamento da República ou manobra discursiva? Uma análise da (in)compatibilidade da legislação infraconstitucional e da argumentação jurídica do STF com o princípio da livre iniciativa nos casos da lei de meia entrada e da lei das mensalidades escolares - ARRAES, Rayana Pereira Sotão (2016)
The Constitution of 1988 expressly guaranteed the State's commitment to promote education, culture, sport and recreation to citizens. Similarly, in order to achieve the goal of promoting the Republic development, it disciplined economic order in particular session and expressly tutored private property and free enterprise. Although the operation of educational and cultural activities has been authorized to the private sector with significant autonomy, leaving the state the role of monitoring the compliance of the exercise of such activity to the values of society - such as the exercise of the social function of property - State interference upon free initiative of the entertainment business sector has been gigantic, on the grounds of democratization of education and culture, as with federal laws 9870/99 and 12.933 / 2013. This paper analyzes such laws, seeking to identify the incompatibility thereof with the Constitution, as well as demonstrating the negative consequences to democracy, the economic environment and access to education and culture, in that it interferes with administrative and financial autonomy of private enterprises of the branches pointed out, to ensure the rights to education and culture, transfering this burden to the private sector.